MULTYCRITERIA DECISION MAKING FOR NOTEBOOK SELECTIONS DENGAN PENDEKATAN ALGEBRA MATRIX - Akmaludin . (JURNAL TEKNIK KOMPUTER AMIK BSI, 2015)
"> ABSTRACT-Advances in computer technology is now proven tohave changed the life style of working, so that workers do not sit inplace but it can do the work anywhere and anytime, becausecomputer technology support to be able to work in mobile. As aworker with high mobility, of course, need a tool such as atablet ora notebook, to be able to help handle any job. The main concern ofthe workers is to choose a notebook that suits their needs andtailored to the devices required in accordance with the Notebookfunction, because it affects the cost to be incurred in the purchaseof products according to their needs. To help overcome thisproblem, then there is one solution that can serve as solutions thatmake up the academic hierarchy model is used to solve the problemof qualitative and quantitative Analytic Hierarchical Process (AHP)with Multi-Criteria Decision Making approach through MatrixAlgebra, while supporting applications to prove results ofmathematical analysis is the application of Expert Choice. Withboth this measure, we can compare the results of calculationsobtained by application of Expert Choice mathematically,especially to prove the value of the resulting eigenvector bothmathematically and with the Expert Choice application gives thesame value. Testing the consistency of the Consistency Ratio (CR)gives an acceptable value according to the rules Saaty should beless than 0.1. For the final selection of the value notebooksynthesize generate sequential priority values as follows 0.299 forAcer Espire 3820T, 0.273 for Lenovo Centre Think Edge, 0.224 forAsus K42JC, and 0.207 for HP Probook 4430S.Keywords: Notebook Selection, Matrix Algebra,Multi-CriteriaDecision Making, Expert Choice.Intisari— Kemajuan teknologi komputer saat ini terbukti telahmengubah gaya hidup dalam bekerja, sehingga pekerja tidakduduk di tempat tetapi dapat melakukan pekerjaan di mana sajadan kapan saja, karena teknologi komputer yang mendukunguntuk bisa bekerja secara mobile. Sebagai seorang pekerjadengan mobilitas tinggi, tentunya membutuhkanseperangkanalat seperti tablet atau notebook, untuk dapatmembantu menangani pekerjaan apa pun. Perhatian utama parapekerja adalah memilih notebook yang sesuai dengan kebutuhanmereka dan disesuaikan dengan perangkat yang dibutuhkansesuai dengan fungsi Notebook, karena mempengaruhi biayayang akan dikeluarkan dalam membeli produk sesuai dengankebutuhannya. Untuk membantu mengatasi masalah ini, makaada satu solusi yang dapat berfungsi sebagai solusi akademisyang menyusun model hirarki yang digunakan untukmemecahkan masalah kualitatif dan kuantitatif dari AnalyticHierarchical Proses(AHP) dengan pendekatan Multi CriteriaDecision Making melalui Aljabar Matrix, sedangkan aplikasipendukung untuk membuktikan hasil analisis secara matematisadalah aplikasi Expert Choice.Dengan kedua alat ukur ini, kita dapat membandingkan hasilperhitungan yang diperoleh secara matematis denganaplikasiExpert Choice, terutama membuktikan nilaiEigenvectoryang dihasilkan baik secara matematismaupundengan Aplikasi Expert Choice memberikan nilai yangsama. Pengujian konsistensi terhadap Consistency Ratio (CR)memberikan nilai yang dapat diterima sesuai aturan Saaty haruskurang dari 0,1. Untuk hasil akhir notebook selection terhadapnilai synthesize menghasilkan nilai prioritas secara berurutsebagai berikut 0.299 untuk Acer Espire 3820T, 0,273 untukLenovo Think Certre Edge, 0,224 untuk Asus K42JC, dan 0,207untuk HP Probook 4430S.Kata kunci: Multi Criteria Decision Making, Notebook Selection,Aljabar Matrix, Expert Choice.